Increased risk of reproductive dysfunction in women prescribed long‐term opioids for musculoskeletal pain: A matched cohort study in the Clinical Practice Research Datalink. (27th June 2018) - Richardson, E.; Bedson, J.; Chen, Y.; Lacey, R.; Dunn, K.M.
Abstract: Background: One‐fifth of primary care attendees suffer chronic noncancer pain, with musculoskeletal conditions the leading cause. Twelve percent of patients with chronic noncancer pain are prescribed strong opioids. Evidence suggests long‐term opioid use is related to hypogonadism in men, but the relationship in women is unclear. Our aim was to investigate reproductive dysfunction in women prescribed long‐term opioids for musculoskeletal pain. Methods: We undertook a matched (matched 1:1; for year of birth, year of start of follow‐up and practice) cohort study of women aged 18–55 years old, with musculoskeletal pain and an opioid prescription in the Clinical Practice Research Datalink (a primary care database) between 2002 and 2013. Long‐term opioid users (≥90 days) were compared with short‐term opioid users (<90 days) for four reproductive conditions (abnormal menstruation, low libido, infertility and menopause) using Cox proportional hazards models. Results: A total of 44, 260 women were included; the median cohort age at baseline was 43 years (Interquartile Range 36–49). Long‐term opioid use was associated with an increased risk of altered menstruation (hazard ratio 1.13 95% CI 1.05–1.21) and with an increased risk of menopause (hazard ratio 1.16 95% CI 1.10–1.23). No significant association was found for libido (hazard ratio 1.19 95% CI 0.96–1.48) or infertility (hazard ratio 0.82 95% CI 0.64–1.06). Conclusions: The risk of menopause and abnormal menstruation was increased in long‐term opioid users. This has implications for clinicians as reproductive dysfunction will need to be considered when prescribing long‐term opioids to women with musculoskeletal conditions. Significance: This is a large‐scale cohort examining the relationship between long‐term opioid use and reproductive dysfunction using a UK national primary care database. There is an increased risk of reproductive dysfunction associated with long‐term opioid use.